Surface Modification of Natural Zeolite Using CTAB And Their Characterization - Maya Sari Ananda Pohan (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Natural zeolites have been widely used for various applications due to their negatively charged frameworks. The utilization of the negatively charged properties of zeolites has contributed significantly to advances in research, particularly in the treatment of heavy metal or cation-containing waste. Wastewater contains not only environmentally harmful cations or heavy metals, but also anions, such as nitrate, phosphate, sulfate, and chloride. Therefore, the zeolite was modified with CTAB to impart a positive surface charge, enabling it to effectively remove anionic species. This research was modified Klaten’s natural zeolite with CTAB. Before modification, the natural zeolite was ground to 200 mesh and first activated using hydrochloric acid. Subsequently, the zeolite was modified by the addition of CTAB at a concentration corresponding to twice its cation exchange capacity. Natural zeolite, activated zeolite, and modified zeolite were characterized using XRD and FT-IR techniques. Based on the obtained results, it was concluded that the modification of Klaten’s natural zeolite was successfully achieved. This is evidenced in the XRD diffractograms, where the CTAB-modified natural zeolite shows a shift in the d-spacing toward lower 2θ values by approximately 0.5° compared to natural zeolite and acid-activated zeolite, indicating an enlargement of the zeolite pores. Furthermore, the FT-IR spectra reveal the presence of characteristic CTAB absorption bands in the modified zeolite.